Optimization of the Melanin Bleaching Method to Improve the Analysis of Malignant Melanoma - Seilla Dinta Yastina; Alimuddin Tofrizal; Yenita Yenita; Henny Mulyani; Pamelia Mayorita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Malignant melanoma is a highly aggressive tumor in which immunohistochemical (IHC) evaluation is often hindered by endogenous melanin, whose brown pigment mimics DAB staining and may lead to false‑positive interpretation. An effective melanin bleaching method is therefore essential to ensure accurate IHC assessment. This study aimed to determine the optimal melanin bleaching protocol for melanoma, particularly for IHC analysis. This preliminary laboratory study used eighteen malignant melanoma samples. Initial bleaching with 0.5% H₂O₂ in PBS or Tris-HCl at 80°C for 4–12 minutes caused marked tissue damage. A second protocol using 5% H₂O₂ in PBS at 50°C for 60, 90, and 120 minutes was tested, followed by a 24‑hour room‑temperature protocol. Tissue integrity, bleaching efficacy, and subsequent HMB45 IHC staining were evaluated. High‑temperature bleaching (protocol 1) produced significant morphological deterioration. Bleaching with 5% H₂O₂ at 50°C effectively removed melanin while preserving tissue structure at 60 and 90 minutes, whereas 120 minutes caused tissue detachment. Room‑temperature bleaching for 24 hours also reduced melanin but resulted in partial tissue damage. HMB45 staining remained strong and interpretable after bleaching at 50°C for 60 and 90 minutes. In conclusion, the most favorable balance between melanin removal, tissue preservation, and IHC quality was achieved using 5% H₂O₂ in PBS at 50°C for 60 minutes. This protocol is recommended as the optimal melanin bleaching method for malignant melanoma tissue.Keywords: melanin bleaching; immunohistochemistry; malignant melanoma